z+344=4224

Multiply both sides of the equation by 44.

44⋅z+344=44⋅4224

Cancel the common factor of 44.

Cancel the common factor.

44⋅z+344=44⋅4224

Rewrite the expression.

z+3=44⋅4224

z+3=44⋅4224

Simplify 44⋅4224.

Cancel the common factor of 4.

Factor 4 out of 44.

z+3=4(11)⋅4224

Factor 4 out of 24.

z+3=4⋅11⋅424⋅6

Cancel the common factor.

z+3=4⋅11⋅424⋅6

Rewrite the expression.

z+3=11⋅426

z+3=11⋅426

Combine 11 and 426.

z+3=11⋅426

Simplify the expression.

Multiply 11 by 42.

z+3=4626

Divide 462 by 6.

z+3=77

z+3=77

z+3=77

z+3=77

Subtract 3 from both sides of the equation.

z=77-3

Subtract 3 from 77.

z=74

z=74

Solve for z (z+3)/44=42/24